A Life Lost, A Lesson Learned: Ecological and Emotional Impacts of a White-Throated Kingfishers Death - Shree, Deepshikha; Mallick, Md Abu Imran; Paik, Sima; Komal, Kumari; Acharjee, Shiladitya; Ansari, Shaba Alam; Pankaj, Smitha (Jurnal Pijar Mipa, 2025)
This study presents a reflective account of a personal encounter with a dead White-Throated Kingfisher (Halcyon smyrnensis) during fieldwork, highlighting the ecological and emotional implications of its death. The incident, likely attributed to heat stress exacerbated by climate change, serves as a poignant reminder of the vulnerability of even resilient species to human-induced environmental pressures. Through a species profile, analysis of environmental stressors, and exploration of anthropogenic threats, this study underscores the urgent need for conservation efforts, climate action, and habitat protection. The emotional impact of the encounter emphasizes the importance of recognizing the intrinsic value of wildlife and the interconnectedness of human and environmental well-being. This research aims to contribute to a deeper understanding of the complex relationships between humans and wildlife, inspiring collective action to mitigate the pressing environmental challenges of our time.